(The Transformation Of Corporate Culture Pt. Telkom, Tbk. Indonesia.) - Bajari, Atwar; Rini Anisyahrini, Rini Anisyahrini (2015)

(untitled)
Corporate culture affects to the productivity and development of an organization in doing business. Therefore, each period, the company must attempt to developed many strategies to create appropriate conditions and climate. Communication played an important role, because the values, rules, and division of work must be integrated through strategy of corporate communications. The corporate communication encourages success of socialization process of values and expected changes. Therefore, manager, media, message content. staff and communication objectives should be designed in order process of transformation running properly. Communication is one of the key of success of the company achieve the goals.